Physical activity towards health and fitness 1 (PATH-FIT 1) : health and wellness, movement education and exercise program - Habana, Antonio Jardin Jr.; Crystal, Leila; Bundalian, Karen T.; Dante, Belen T. (Manila : Mindshapers Co., Inc., 2023)
"Movement is one of the significant features of all living things. It is a fundamental aspect of human life. In physical education, we learn to move and we move to learn. Move to learn is the context of physical activity as the means for learning, while learn to move embodies the learning of skills and techniques and the acquisition of understanding that are requisites to participation in a variety of physical activities that include exercise, games, sports, dance and recreation. It is in this light that this book is written. It includes chapters that highlight activities like locomotor movements, non-locomotor movements and mobility training for students' movement competence. It also values the importance of healthy habits which will make the individual free from sickness and infirmity."
Includes references.
English.
Keywords: Physical fitness; Physical education